Bacterial septicemia in juvenile tiger shrimp, Penaeus monodon, cultured in Malaysian brackishwater ponds - Anderson, I. G.; Shamsudin, Mariana Nor; Mohamed Din, Mohamed Shariff; Nash, G. (Asian Fisheries Society, 1988)
Penaeid bacterial septicemia in juvenile market-size tiger shrimp, Penaeus monodon, on three brackishwater pond farms in Johore, Malaysia, is described. Histologically, tissue changes of experimental Gram-negative bacterial infections in marine crustaceans were observed in affected shrimp. Vibrio alginolyticus, V. parahaemolyticus, Pseudomonas sp., and other Gram-negative bacteria were isolated in low numbers from the hemolymph. The diagnosis and control of penaeid bacterial septicemia are discussed.